The Implementation Tandur Quantum Teaching Learning Model to Improve Social Learning Achievement - Habaridota, Maha Lastasa Buju Basafpipana (Universitas Pendidikan Ganesha, 2020)
Social studies is a subject with memorizing learning that scared some students of it is applied without considering students need and students’ various learning style. Indirectly this situation would affect the students’ learning outcomes. Besides, there are some difficulties happen in social studies for advance class, such as: a) Students have low ability on developing traits and attitude in daily life; b) IPS only taught in a very limited time. So, it is hard to cover all the important values. Therefore, learning process should emphasize on an enjoyable process that relates to ability and Students learning style. The purpose of this research is to analyze the impact of the Quantum Teaching Technique TANDUR towards social studies for elementary school students' learning achievement. The type of research is the basic pattern of The Posttest Only Control Group with a quasi-experiment. The research Will conduct on the sixth grade of Elementary School Students in SD 07 Sungai Raya Kubu Raya Regency, Kalimantan Barat. The population of the research consists of 106 Students, with 70 Students as the sample. Data analysis used in this research is MANOVA (Multivariant Analysis of Variance) assisted by SPSS 17.00 by windows. The result shows that IPS learning achievement between Students with Quantum Teaching Technique TANDUR learning model is more significant than Students with a conventional model (F 1 3.682 and sig = 0,000; p < 0,05). This research would give an overview of teacher's innovation by applying various teaching models to create meaningful learning to improve Students learning achievement.